Implementasi Pendidikan Multikultural dalam Pembelajaran Ilmu Pengetahuan Sosial di SMP N 30 Semarang - Lutfi, Muhammad; Lestari, Puji (Universitas Negeri Semarang, 2021)
SMP Negeri 30 Semarang is a school that implements multicultural education, so it needs to be studied more deeply about at the implementation of multicultural education in social studies learning. This study used qualitative research methods. The results showed that: (1) The implementation of multicultural education in social studies learning at SMP Negeri 30 Semarang begins with lesson planning. The implementation of learning is open, democratic, student-centered which emphasizes the equality and fairness of students and respects each individual. Learning evaluation leads to cognitive, effective and psychomotor by using their own instruments in assessing multicultural attitudes. (2) Supporting factors in the implementation of multicultural education, namely the school environment and climate, learning materials and methods, school programs and activities, extracurricular activities (talents and interests), and the awareness of students. Inhibiting factors are the limitations of social studies material on diversity, media limitations on diversity, there are still some students who mock their friends, the lack of boards or writing about diversity